Assessment of a decontamination process for dioxins and PCBs from fish meal by hexane extraction and replacement of fish oil. (12th February 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on the assessment of a decontamination process for fish meal. This process entails solvent (hexane) extraction of fish oil from fish meal to remove dioxins (polychlorinated dibenzo‐ p ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs)) as well as dioxin‐like (DL‐) and non‐dioxin‐like (NDL‐) polychlorinated biphenyls (PCBs) followed by replacement with decontaminated fish oil. All feed decontamination processes must comply with the acceptability criteria specified in the Commission Regulation (EU) 2015/786. The data provided by the feed business operator were assessed with respect to the efficacy of the process, absence of solvent residues, and on information demonstrating that the process does not adversely affect the nature and characteristics of the product. According to data provided, the process was effective in removing PCDD/Fs and DL‐PCBs by approximately 70% and NDL‐PCBs by about 60%. The data showed that it is possible to meet the current EU requirements with respect to these contaminants, provided that the level of contamination of untreated fish meal is within the range of the tested batches. It is unlikely that hazardous substances (i.e. hexane) remain in the final product. The Panel considered that there is no evidence that fish oil extraction followed by replacement with decontaminated fish oil leads to detrimental changes in the nutritional composition of the fish meal, although some beneficial constituents (e.g. lipophilic vitamins) might be depleted. The feed business operator submitted information to demonstrate safe disposal of the waste material. The CONTAM Panel concluded that the proposed decontamination process to remove dioxins (PCDD/Fs) and PCBs from fish meal by means of solvent extraction and fish oil replacement was assessed to be compliant with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015.